2023
DOI: 10.3390/ma17010123
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Flexible Mechanical Force Sensors for Healthcare and Diagnosis

Hang Zhang,
Yihui Zhang

Abstract: Over the past decade, there has been a significant surge in interest in flexible mechanical force sensing devices and systems. Tremendous efforts have been devoted to the development of flexible mechanical force sensors for daily healthcare and medical diagnosis, driven by the increasing demand for wearable/portable devices in long-term healthcare and precision medicine. In this review, we summarize recent advances in diverse categories of flexible mechanical force sensors, covering piezoresistive, capacitive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 282 publications
(443 reference statements)
0
2
0
Order By: Relevance
“…The flexibility and ability of these devices to withstand mechanical deformations make them a viable alternative compared to conventional electronic components, which are typically rigid. This technological advancement has found applications in various sectors, such as the automotive industry [1], biomedical field [2,3], and the development of robotic skins [3][4][5], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexibility and ability of these devices to withstand mechanical deformations make them a viable alternative compared to conventional electronic components, which are typically rigid. This technological advancement has found applications in various sectors, such as the automotive industry [1], biomedical field [2,3], and the development of robotic skins [3][4][5], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on these types of systems have shown notable characteristics, such as high sensitivity [3,6], stretchability [6], response rate [3,6], stability [6], and low fabrication cost [6]. Regarding force sensors [7][8][9], they can employ various measurement techniques based on phenomena such as piezoelectric, piezocapacitive, triboelectric, or piezoresistive [1,6]. In particular, piezoresistive pressure sensors transform input pressure into a change in resistance in the device [6].…”
Section: Introductionmentioning
confidence: 99%